Analisis Kesulitan Belajar Siswa Kelas III pada Mata Pelajaran Matematika di SDN 9 Ampenan Tahun Pelajaran 2022/2023 - Geka Setia Auliah; Darmiany Darmiany; Nurhasanah Nurhasanah (Griya Journal of Mathematics Education and Application, 2023)
This study aims to determine the types of mathematics learning difficulties experienced by students and the improvement efforts made by teachers to overcome mathematics learning difficulties for third-grade students of SDN 9 Ampenan. This research is qualitative research with the descriptive method and uses the procedure of implementing the diagnosis of learning difficulties. The research subjects were 6 third-grade students who had difficulty learning mathematics and third-grade teachers. Methods of data collection using interviews, observation, and documentation. Data analysis using Interactive Analysis Method. The results showed that students had difficulty learning the subject of arithmetic operations of addition, subtraction, multiplication, and division. The types of mathematics learning difficulties experienced by students are difficulties in understanding mathematical concepts, difficulties in calculations, difficulties in understanding mathematical symbols, and difficulties in working on story problems. Improvement efforts made by classroom teachers are peer tutors, special tutoring, remedial or repairs to students who have grades below the KKM, and communicating and collaborating with parents. To overcome difficulties in learning mathematics that come from within students, it is recommended to create conditionals (reinforcement, rewards, encouragement), while difficulties that come from outside students are carried out by completing facilities and infrastructure in the learning process and using varied methods.